Restaurant Governance in the Pandemic Period Implementation of GCG at the Warong Bakar Bakar Restaurant - Habelana Lucia Goni; Denny Tewu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Restaurants as food and beverage providers are included in the hospitality industry that sells hospitality services and are organized commercially by applying general business principles. Hospitality services mean a good relationship between guests and service providers. The Warong Bakar Bakar (WBB) restaurant as part of the hospitality industry must follow the principles of this industry and combine it with good corporate governance in order to produce the desired results.During the pandemic, restaurant governance in addition to other GCG aspects is more emphasized on the responsibility side in the form of CSR (Corporate Social Responsibility) to the community and to employees, by enforcing special guidelines for the restaurant industry through Ministry of Tourism & Creative Economy Regulation No. 13 2020 concerning Guidelines for the Implementation of Hygiene, Health, Safety, and Environmental Sustainability in Restaurants/Restaurants during the handling of the 2019 CoronaVirus Disease Pandemic. With this thesis that uses fish bone analysis, it is hoped that it will provide a solution for business problems in the hospitality industry in order to survive during the Pandemic, where this sector is one of the ones that will feel the biggest impact.